A pulmonary enteric adenocarcinoma patient harboring a rare EGFR exon 19 P753S mutation: Case report and review - Xu, Xiaohu; Chen, Dong; Wu, Xiao; Wang, Qi (Frontiers in Oncology, 2022)
Pulmonary enteric adenocarcinoma (PEAC) is a rare subtype of non-small cell lung cancer (NSCLC), accounting for about 0.6% of all primary lung adenocarcinoma. Although Epidermal Growth Factor Receptor (EGFR) mutation is common in primary lung adenocarcinoma, it is rarely reported in PEAC. This case report describes a PEAC patient with co-mutations of EGFR, KRAS, and TP53, being treated with immunotherapy combined with chemotherapy. A 69-year-old man complaints of cough and expectoration with bloody sputum for 2 weeks. An lung enhanced CT scan showed a massive soft tissue shadow, about 46×35mm in the lower lobe of the right lung. The neoplasm sample in the lower lobe of the right lung was obtained using CT-guided fine-needle aspiration (FNA). Immunohistochemical assays showed that the tumor was positive for CK7, CDX-2, C-MET and villin. Gastroscopy and rectocolonoscopy had been performed respectively to exclude a diagnosis of colorectal adenocarcinoma. The patient was finally diagnosed with pulmonary intestinal adenocarcinoma. Next-generation sequencing analysis (NGS) showed a rare EGFR 19 exon missense mutation (c.2257C>T, p.P753S) , KRAS 2 exon missense mutation (c.35G>T, p.G12V) and TP53 5 exon missense mutation (c.401T>C, p.F134S). Lung enhanced CT showed that the tumor shrank after 4 cycles of chemotherapy combined with immunotherapy. We hope that this case report can increase the understanding of this rare type of tumor and provide new molecular indications for diagnosis and individualized treatment. Furthermore, combination with chemotherapy and immunotherapy seems to be an effective therapy for PEAC. Whether the use of immunotherapy can provide clinical benefits needs to be further explored with more samples in future studies.